Radioautographic study of mesenchymal cell activity in the secondary palate of the rat - Cleaton-Jones, P. (My University, 1976)
Fifteen µCi of ³H-thymidine was injected into the amniotic cavity of fetal rats from day 15 to 19 postinsemination. Analysis of radioautographs from these rats did not show increased mesenchymal cell activity to be responsible for medial rotation of the palatal shelves. Variations in cell activity in the older fetuses were mainly due to developing bone and glands.
Keywords: Autoradiography; Mesoderm/cytology; Palate/embryology